Report on freshwater Catenulida (Platyhelminthes) from Sweden with the description of four new species - Larsson, Karolina; Willems, Wim (Zootaxa, 2010)
This contribution is one of the very first reports on Swedish species of freshwater Catenulida, a group of free-living, small flatworms. A total of 13 species were collected from 33 localities all over the country. Four species, all belonging to the taxon Stenostomum, are new to science. S. gotlandense n. sp., found on Gotland, has small ciliated pits located more posteriorly than other species of Stenostomum, large anterior brain lobes and a large mouth opening with peculiar wrinkles of the proximal rim of the pharynx. S. handoelense n. sp., from Jämtland, has long ciliated pits and a mobile prostomium with a lined appearance due to “metamerical” anterior brain lobes. S. heebuktense n. sp., from Bohuslän, has small ciliated pits and an extremely large and muscular pharynx which, in living animals, is bluish. S. steveoi n. sp., found in the provinces Bohuslän and Småland, has small ciliated pits and a large rectangular mouth opening. The remaining 9 species are illustrated and commented upon where necessary. For the sake of completeness three undescribed species are mentioned. Some general remarks on identification of catenulid species are given.